2020
DOI: 10.2147/rmhp.s257834
|View full text |Cite
|
Sign up to set email alerts
|

<p>Campus Policy on Tobacco Prohibition and Tobacco Use among Youth in Sub-Saharan Africa: An Investigation Based on the Perspectives of School Personnel</p>

Abstract: Background: Schools in sub-Saharan Africa respond to the widespread use of tobacco among youth with the tobacco-prohibition policies. This study empirically examined the impact of the strength of campus tobacco-prohibition policies on tobacco use among youth across 20 sub-Saharancountries. Methods: This study used data from the Global School Personnel Survey across 20 sub-Saharan countries during 2005-2011. Respondents comprised 7,365 school personnel (valid sample size) from Cameroon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… 52 For short-term deaths (eg, day-10 and day-20 deaths), developing countries show significant additional mortality risks. Besides inadequate health systems in developing countries, this finding may also point to greater prevalence of tobacco use in developing countries, where the poor, less educated, and illiterate account for a higher population proportion, 44 , 45 as smoking-related comorbidities have been found to be closely associated with the severity of symptoms of this pandemic. 39 Further, when taking sex difference and age subgroups into consideration, countries with a higher proportion of older males face higher risks, among which those with a higher proportion of males aged 70–74 years are at highest risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 52 For short-term deaths (eg, day-10 and day-20 deaths), developing countries show significant additional mortality risks. Besides inadequate health systems in developing countries, this finding may also point to greater prevalence of tobacco use in developing countries, where the poor, less educated, and illiterate account for a higher population proportion, 44 , 45 as smoking-related comorbidities have been found to be closely associated with the severity of symptoms of this pandemic. 39 Further, when taking sex difference and age subgroups into consideration, countries with a higher proportion of older males face higher risks, among which those with a higher proportion of males aged 70–74 years are at highest risk.…”
Section: Discussionmentioning
confidence: 99%
“… 34 Studies have demonstrated higher prevalence of tobacco use in areas with great social vulnerability, where populations face poverty, and the less educated and illiterate account for a large percentage. 44 , 45 Therefore, in the initial phase of the pandemic, where the run on medical resources is yet to happen, developed areas may have the advantage of completer health systems and better economic support.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The policy intervention has long been insufficient to protect the health of children and youth in underdeveloped areas ( Li, Yuan & Zeng, 2020a ). During the period of cholera, the rich had a lower risk of getting infected due to having more access to healthy drinking water ( Clouston et al, 2016 ).…”
Section: Literature Reviewmentioning
confidence: 99%